Controlling the enrichment location of brush grafted multi-walled carbon nanotubes at the interface of various polymer blends. (3rd January 2022) - Zhang, Haimo; Zhong, Jun; Zhang, Xinyue; Shi, Xuanyu; Yang, Li; Sun, Shihao; Zuo, Min; Song, Yihu; Zheng, Qiang
Abstract: Guided by a phase diagram we proposed recently, the identical multi-walled carbon nanotubes (MWNTs) grafted with poly(methyl methacrylate) (PMMA) brush may be located at the interface of various PMMA-based blends. Hence, we grafted PMMA brushes with the molecular weight less than that of PMMA matrix roughly on the surface of MWNTs by Cu(0)-mediated living radical polymerization, in which DMF was selected as a good reaction solvent of MMA and proper dispersant of 2-bromoisobutyrate functional MWNTs. Such modified MWNTs can be mostly located at the interface of PMMA/styrene-acrylonitrile copolymer (SAN), PMMA/polystyrene (PS), PMMA/polyvinyl acetate (PVAc) and PMMA/poly( α -methyl styrene-co-acrylonitrile) (MSAN) blends. It can provide a path as a reference template to prepare various nanocomposites with nanoparticles self-assembling at the interface of binary polymer blends. Graphical abstract: Image 1 Highlights: The location of multi-walled carbon nanotubes (MWNTs) can be controlled by grafting homopolymer-brush. The location can be quantitatively controlled by grafted molecular weight. The grafted molecular weight can be well controlled by Cu(0)-mediated living radical polymerization. The identical grafted MWNT can be located at the interface of various PMMA-based blends.